Singapore Malays : being ethnic minority and Muslim in a global city-state - Hussin Mutalib, 1949- (London : Routledge, 2012)
'The Malay population makes up Singapore's three largest ethnic groups. This book provides an analysis of the debates on religion, politics and citizenship of Malay Muslims in contemporary Singapore. Comprehensively and convincingly argued, the author examines their disadvantaged circumstances in the fields of politics, education, social mobility, and freedom of religious expression.'--Publisher's description.
Includes bibliographical references (p. [190]-200) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Malays -- Singapore; Muslims -- Singapore; Singapore -- Ethnic relations